Increased Expression and Modulated Regulatory Activity of Coinhibitory Receptors PD‐1, TIGIT, and TIM‐3 in Lymphocytes From Patients With Systemic Sclerosis. Issue 4 (7th March 2018) - Fleury, Michelle; Belkina, Anna C.; Proctor, Elizabeth A.; Zammitti, Christopher; Simms, Robert W.; Lauffenburger, Douglas A.; Snyder‐Cappione, Jennifer E.; Lafyatis, Robert; Dooms, Hans
Abstract : Objective: Immune dysfunction is an important component of the disease process underlying systemic sclerosis (SSc), but the mechanisms contributing to altered immune cell function in SSc remain poorly defined. This study was undertaken to measure the expression and function of the coinhibitory receptors (co‐IRs) programmed cell death 1 (PD‐1), T cell immunoglobulin and ITIM domain (TIGIT), T cell immunoglobulin and mucin domain 3 (TIM‐3), and lymphocyte activation gene 3 (LAG‐3) in lymphocyte subsets from the peripheral blood of patients with SSc. Methods: Co‐IR expression levels on subsets of immune cells were analyzed using a 16‐color flow cytometry panel. The functional role of co‐IRs was determined by measuring cytokine production after in vitro stimulation of SSc and healthy control peripheral blood mononuclear cells (PBMCs) in the presence of co‐IR–blocking antibodies. Supernatants from cultures of stimulated PBMCs were added to SSc fibroblasts, and their impact on fibroblast gene expression was measured. Mathematical modeling was used to reveal differences between co‐IR functions in SSc patients and healthy controls. Results: Levels of the co‐IRs PD‐1 and TIGIT were increased, and each was coexpressed, in distinct T cell subsets from SSc patients compared to healthy controls. Levels of TIM‐3 were increased in SSc natural killer cells. PD‐1, TIGIT, and TIM‐3 antibody blockade revealed patient‐specific roles of each of these co‐IRs in modulating activation‐induced T cell cytokine production. In contrast to healthy subjects, blockade of TIGIT and TIM‐3, but not PD‐1, failed to reverse inhibited cytokine production in SSc patients, indicating that enhanced T cell exhaustion is present in SSc. Finally, cytokines secreted in anti–TIM‐3–treated PBMC cultures distinctly changed the gene expression profile in SSc fibroblasts. Conclusion: The altered expression and regulatory capacity of co‐IRs in SSc lymphocytes may contribute to disease pathophysiology by modulating the cytokine‐mediated cross‐talk of immune cells and fibroblasts at sites of inflammation and/or fibrosis.